Aqueous colloidal processing of nano-SiC and its nano-Y3Al5O12 liquid-phase sintering additives with carbon nanotubes. Issue 13 (November 2015) - Candelario, Victor M.; Moreno, Rodrigo; Shen, Zhijian; Ortiz, Angel L.
Abstract: Carbon nanotubes (CNTs) have occasionally been observed to benefit the aqueous colloidal processing of nano-SiC with its nano-Y3 Al5 O12 liquid-phase-sintering additives. Experimental evidence is here presented for a broad set of CNTs with different morphology and/or surface functionalization confirming that CNTs (7 vol.% addition), regardless of their features, prevent the coagulation of these nanoceramic suspensions, whence it is inferred that aqueous colloidal processing is well-suited for the environmentally friendly preparation of the homogeneous mixtures of nanoceramic particles and CNTs required for the fabrication of CNT-reinforced ceramic matrix nanocomposites. Furthermore, it is shown that surface-functionalized CNTs seem to work better than deflocculated CNTs for the preparation of stable concentrated colloidal suspensions, whose rheological properties are in general very close, but with thinner CNTs being nonetheless preferable. Finally, the feasibility is demonstrated of fabricating SiC/CNT nanocomposites by aqueous colloidal processing followed by liquid-phase assisted spark-plasma sintering.